Elucidating the interaction and toxicity of cadmium and cerium on the growth of maize seedlings: Insights from morpho-physiological and biochemical analysis - Huihong Zhang; Ying Jiang; Qiujuan Jiao; Lantao Li; Gezi Li; Yinglong Chen; Evgenios Agathokleous; Chandra Shekhar Seth; Erkai He; Yi Wang; Shiying Li; Shiliang Liu; et al. (Ecotoxicology and Environmental Safety)
The exploitation of rare earth elements (REEs) is often accompanied by heavy metal contamination. However, our understanding regarding the growth responses of plants to the co-existence of REEs and heavy metals (HMs), remains limited. In this study, cerium (Ce) and cadmium (Cd) were selected as representatives of REEs and HMs to investigate their interactive effects on maize growth through multiple model analyses. The results revealed that both Cd and Ce induce oxidative injuries by increasing reactive oxygen species (ROS) content in a dose-dependent manner. Ce can enhance chlorophyll content while reducing leaf yellowing induced by Cd. The addition of 10 and 100 mg· L−1 Ce significantly increased the Chla content in 50 μM Cd sets by 52.2 % and 50.2 % compared to Cd50Ce0 treatment, respectively. Evaluation of the physiological and biochemical effect level index (PBELI) showed that the primary interaction mode of Cd and Ce was antagonism. The co-existence of Cd (50 μM) and Ce (100 mg· L−1) poses a higher ecological risk than Ce alone. These results demonstrated that combined exposure to Cd and Ce exhibited diverse effects in mitigating the inhibition of maize growth, thereby improving our understanding of phytotoxicity resulting from metal mixtures in the environment.